AB0039 The Frequency of Acpa-Specific B Cells in the Circulating Memory B Cell Pool of Patients with Rheumatoid Arthritis. (10th June 2014) - Saunders, U.; Fassbinder, T.; Becker, H.; Jung, E.; Mickholz, E.; Jacobi, A.M.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease characterized by the presence of autoantibodies (AA) such as rheumatoid factor (RF) and anti-citrullinated peptide antibodies (ACPAs). These AA do not only play a pivotal role in diagnostics, but also in pathogenesis of RA. AA can be secreted by long-lived plasma cells homing to the bone marrow or by newly generated plasma cells derived from the memory B cell pool. Objectives: To determine the frequency of ACPA-specific cells within the circulating memory B cell pool of ACPA-positive RA patients. Methods: In order to compare the frequency of anti-cyclic citrullinated peptid (CCP) and anti-mutated citrullinated vimentin (MCV) antibody specific B cells within the memory B cell pool of 7 CCP- and 7 MCV-positive patients with RA and 4 or 6 normal healthy subjects (NHS) we analyzed antibody secretion by ELISPOT after transforming memory B cells into plasmablasts (PB). For comparison we determined the frequency of tetanus toxoid (TT)-specific B cells in the circulating pool of memory B cells of 8 TT-vaccinated NHS. CD27 + memory B cells were isolated from peripheral blood samples. After polyclonal activation for 4 days the percentage of PB (CD27 ++ ) was determined by flow cytometry. To determine the frequency of anti-CCP, anti-MCV and anti-TT antibody secreting cells ELISPOT assays (IgM, IgG, IgA) were performed. Results: Flow cytometric analysis revealed that after 4 days 62±11% (RA n=14) and 62±13% (NHS n=18) of all viable cells in culture adopted the phenotype of CD27 ++ PB. The frequencies of antigen-specific B cells of all individuals are shown in Table 1 . In contrast to NHS, 71.4% of CCP-positive and 28.6% of all MCV-positive RA patients had detectable frequencies of CCP- or MCV-specific IgG antibody secreting cells (ASC). In these individuals the frequencies of ACPA-secreting cells were lower than the frequency of anti-TT-specific IgG ASC in TT-vaccinated NHS, who all had detectable frequencies of TT-specific IgG ASC (CCP: 0.22±0.21%, MCV: 0.34±0.40, TT: 0.9±0.7). Conclusions: Using this approach, ACPA-specific B cells can be detected in the circulating memory B cell pool only in a subset of ACPA-positive RA patients. In the remaining patients, ACPA-specific B or plasma cells might home in the bone marrow or inflamed joints. Disclosure of Interest: U. Saunders Grant/research support: Chugai Pharmaceutical Co., Ltd., T. Fassbinder: None declared, H. Becker: None declared, E. Jung: None declared, E. Mickholz: None declared, A. Jacobi Grant/research support: Chugai Pharmaceutical Co., Ltd. DOI: 10.1136/annrheumdis-2014-eular.2229